2012
DOI: 10.1016/j.artres.2012.09.204
|View full text |Cite
|
Sign up to set email alerts
|

P4.57 Stiffness of the Large Arteries in Individuals With and Without Down Syndrome

Abstract: Background: Down syndrome is known to cause premature aging in several organ systems. However, it remains unclear whether this aging effect also affects the structure and function of the large arterial trunks. In this controlled study, the possibility of changes in the large arteries due to aging was evaluated in patients with Down syndrome. Methods: Eighty-two subjects of both genders were selected. The Down syndrome group had 41 active subjects consisting of 19 males and 22 females (mean age 21 ± 1, range 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…These findings are in accordance with the only two previous studies assessing subclinical atherosclerosis in individuals with DS based on cIMT and PWV. Consistent with Rodrigues and colleagues, we found that chronic low BP values could play a key role in reducing arterial stiffness in adults with DS. These findings confirm the importance of BP as the main determinant of arterial stiffness, both in adults with DS and in adults without DS, although genetic differences in arterial wall architecture and function, which affect endothelial function and elasticity, are also important.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are in accordance with the only two previous studies assessing subclinical atherosclerosis in individuals with DS based on cIMT and PWV. Consistent with Rodrigues and colleagues, we found that chronic low BP values could play a key role in reducing arterial stiffness in adults with DS. These findings confirm the importance of BP as the main determinant of arterial stiffness, both in adults with DS and in adults without DS, although genetic differences in arterial wall architecture and function, which affect endothelial function and elasticity, are also important.…”
Section: Discussionsupporting
confidence: 85%
“…Information on subclinical vascular damage in individuals with DS is scarce, and only two studies have attempted to demonstrate a lower frequency of atherosclerosis in this population. Draheim and colleagues found lower cIMT values in 52 individuals with DS compared with 52 controls matched for sex and age, while Rodrigues and colleagues failed to find any difference in PWV values in adults with DS compared with nontrisomic adults.…”
mentioning
confidence: 99%
“…These include: (a) the integumentary system (i.e., the skin and its appendages), reflected by skin wrinkling and alopecia [Lott, ; Martin, ; Brugge et al, ]; (b) the endocrine system; reflected by earlier menopause in women [Patel et al, ; Schupf et al, , ; Hawli et al, ]; (c) the sensory system [Krinsky‐McHale et al, ]; (d) the musculoskeletal system [van Allen et al, ; Barnhart and Connolly, ]; (e) the immunological system [Lima et al, ], and (f) the neurological system (i.e., seizures, AD) [Lott et al, ]. (In contrast, conditions such as atherosclerosis, ischemic cardiac problems, hypertension, and adult‐onset solid cancers are uncommonly found in people with DS [Lott and Head, ; Rodrigues et al, ]). One of the most troublesome aspects of premature aging in people with DS is the early development of the neuropathology of AD [Mann et al, ; Lott and Head, ; Zigman and Lott, ] and the potential progression to the clinical signs of AD some years or decades later [Schupf, ; Beacher et al, ; Lott et al, ; Lott, ].…”
Section: Accelerated Aging In Dsmentioning
confidence: 99%
“…A body of research has indicated that hypertension and the development of ischemic cardiac disease are not common in adults with DS [Lott and Lai, ; Morrison et al, ; Kapell et al, ; Rodrigues et al, ], with one conspicuous exception, 25.5% of adults with DS over 50 were found to have hypertension in a study conducted in Findland [de Winter et al, ]. Subsequent to the surgical correction of congenital heart defects through childhood and adulthood, people with DS are at low risk for cardiac disease.…”
Section: Accelerated Aging In Dsmentioning
confidence: 99%
See 1 more Smart Citation